1998
DOI: 10.1021/jp9730252
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Acid-Catalyzed Hydrolysis of a Polyphosphate in Water

Abstract: The zeroth-order reaction of the hydrolysis of sodium polyphosphate in water at pH = 0 can be explained assuming the formation of a pentacovalent terminal phosphorus intermediate. A terminal unit is activated for hydrolysis by protonation of the double-bond oxygen on that unit followed by a nucleophilic attack of water. Proton transfer from an OH group to a P−O−P bond breaks the bond, thereby shortening the phosphate polymer. A mathematical equation is developed to explain the reaction order of the hydrolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 6 publications
0
37
3
Order By: Relevance
“…It was found that P3 is the preferred intermediate hydrolysis product rather than P1, contrary to the hydrolysis mechanism proposed before 81. …”
contrasting
confidence: 82%
“…It was found that P3 is the preferred intermediate hydrolysis product rather than P1, contrary to the hydrolysis mechanism proposed before 81. …”
contrasting
confidence: 82%
“…Under low collision-energy conditions, the spectrum displayed the fragment at m/z 159, HP 2 O 6 À , corresponding to the loss of a water molecule. At slightly higher collision energies, it displayed the ion at m/z 79, PO 3 À , corresponding to the loss of H 3 PO 4 .…”
Section: Resultsmentioning
confidence: 99%
“…(3)] considering that the enthalpy change of the hydrolysis reaction (vide infra) was computed to be endothermic by nearly 23 kcal mol These results suggest that H 3 P 2 O 7 À ions investigated by TQ/MS have the structure of the linear pyrophosphate anion I, the only structure which is consistent with the highenergy loss of the H 2 PO 4 À fragment. Furthermore, the appearance of both the ions at m/z 159 and m/z 79 at comparable energy thresholds allows the presence of the [HP 2 O 6 …”
Section: Discussionmentioning
confidence: 99%
“…Temperature is a vital factor influencing polyphosphate hydrolysis because high temperature increases the amount of activated molecules in enzyme‐catalysed biological reactions (De Jager & Heyns, ). Wang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Temperature is a vital factor influencing polyphosphate hydrolysis because high temperature increases the amount of activated molecules in enzyme-catalysed biological reactions (De Jager & Heyns, 1998). Wang et al (2015) reported that the time needed for the complete hydrolysis of pyrophosphate was within 4 days at 35°C and within 6 days at 30°C conditions; in contrast, only 84%-95% of the pyrophosphate was hydrolysed after 10 days at 20°C and 25°C.…”
Section: Discussionmentioning
confidence: 99%